Faktor-faktor yang mempengaruhi amalan kerja berprestasi tinggi dalam kalangan pensyarah UUM, Sintok - Aqilah, Abdul Manaf (2014)
High performance work system is one of the way organizations to prepare and restructuring back the works, the human source, technology, and information in the process to achieve high achievement. This study was conducted to find out the factors that influence the high performance work system and used quantitative method in determining the relationship between all the independent variables (High Performance Work System Factors) and dependent variable (High Performance Work System). This study involved 130 respondents from Universiti Utara Malaysia. Researcher has distributed 274 sets of questionnaire to the respondents but researcher only received back 130 completed questionnaires. The questionnaire contains of 59 items that have used seven point Likert scale. Each hypothesis was tested using Statistics Package for Social Science (SPSS) version 21.0. The obtained data were analyzed using descriptive analysis and inferential analysis namely correlation and regression. 21 hypotheses were formed after performed the factor analysis and the inferential analysis was used to determine the relationship between independent variables and dependent variable. The results of the study showed that the work life balance (role), organizational culture (improvement) and organizational culture human resources related to the high performance work system (human resource management orientation). The dependent variable factor high performance work system (workers involvement orientation) influenced by the work life balance(work load), work life balance (role), organizational culture (human resources),organizational culture (environment), organizational culture (autonomy) and work ethics. Following that, high performance work system (workers attitude orientation) was influenced by the work ethic and organizational culture (human resource)